Coated Biodegradable Zinc Lithium Alloys: Development and Characterization of Co-Doped Strontium Copper Tricalcium Phosphate Coating for Antimicrobial Applications - Rau, Julietta V.; De Bonis, Angela; Curcio, Mariangela; Barbaro, Katia; Fosca, Marco; Fadeeva, Inna V.; Cardoso, Giovana Collombaro [UNESP]; Teghil, Roberto; Slonskaya, Tatiana K.; Zheng, Yufeng (MDPI, 2024)
Zinc biodegradable implants represent a revolutionary advancement in medical technology, offering a promising alternative to titanium and stainless-steel implants and avoiding the need for secondary surgeries for removal. In this study, we aimed to fulfil the clinical demand for biodegradable implant materials by applying a coating of double-doped strontium and copper resorbable tricalcium phosphate (SrCu-TCP) onto a zinc-lithium (Zn-Li) biodegradable alloy using the Pulsed Laser Deposition method. The coated surfaces were thoroughly characterized using X-ray Diffraction, Fourier Transform Infrared Spectroscopy, Atomic Force Microscopy, and Scanning Electron Microscopy coupled with Energy Dispersive X-ray. Microbiology experiments were conducted to assess the inhibitory effects on the growth of various bacteria strains, including gram-positive Staphylococcus aureus and Enterococcus faecalis, gram-negative Pseudomonas aeruginosa and Escherichia coli, as well as the fungus Candida albicans. The obtained results showed that the roughness of the Zn-Li alloy increased from 91.8 ± 29.4 to 651.0 ± 179.5 nm when coated with SrCu-TCP. The thickness of the coating ranged between 3–3.5 µm. The inhibition of growth for all four bacteria strains and the fungus was in the range of 24–35% when cultured on SrCu-TCP coated Zn-Li samples. These findings suggest that the developed coatings are promising candidates for applications requiring inhibition of microorganisms.
Keywords: biodegradable alloys; biodegradable coatings; coatings; copper and strontium co-doped tricalcium phosphate; copper and strontium doped tricalcium phosphate; tricalcium phosphate coatings; Zn-Li alloy